Primary care physicians' attitudes and knowledge regarding medical cannabis and willingness to prescribe it: the Israeli experience. (3rd September 2021) - Adler, Limor; Zacay, Galia; Schonmann, Yochai; Azuri, Joseph; Yehoshua, Ilan; Vinker, Shlomo; Shani, Michal; Heymann, Anthony D; Hoffman, Robert
Abstract: Background: Use of medical cannabis (MC) in Israel has increased since its regulatory approval in 2016. Currently, more than 1% of Israeli adults are treated with MC; this requires primary care physicians (PCPs) to be familiar with this treatment option. Objectives: We assessed the attitudes and knowledge of Israeli PCPs toward MC and evaluated their willingness to prescribe it for different medical conditions. Methods: A cross-sectional survey which was distributed to PCPs in Israel. Physicians were asked about their opinions, knowledge, and willingness to prescribe MC. Results: Two hundred and one PCPs answered the questionnaire. Their average age was 47 years (±11.2), 71% were specialists. 51% of the respondents thought that MC is an effective treatment. 63% replied that they had little knowledge and 75% indicated that they would like to deepen it. 61% of the respondents were willing to initiate an MC treatment for a dying patient, while less than 50% were willing to initiate MC treatment for various other conditions. Most respondents indicated that they were willing to renew a prescription for any approved medical condition. Willingness to prescribe MC increased for physicians who agreed that MC was effective (odds ratio [OR] 21.9, 95% confidence interval [CI] 2.40–200.85), for physicians who strongly agreed with the statement that they had sufficient knowledge (OR 5.0, 95% CI 1.58–15.83) and for residents compared with specialists (OR 4.0, 95% CI 1.52–10.73). Conclusions: Our survey revealed PCPs' differing opinions and insufficient knowledge regarding treatment with MC. These findings suggest that continuing medical education regarding MC is needed. Lay Summary: Use of medical cannabis (MC) in Israel has increased substantially since its regulatory approval in 2016. Currently, more than 1% of Israeli adult population receive MC; this requires primary care physicians (PCPs) to be familiar with this treatment option. We assessed the attitudes and knowledge of Israeli PCPs toward MC and evaluated their willingness to prescribe it for different medical indications. Two hundred and one PCPs answered our questionnaire. 51% of the respondents thought that MC was an effective treatment. 63% of physicians stated that they had little knowledge regarding MC and 75% indicated that they would like to deepen it. 61% of the respondents were willing to initiate MC treatment for a dying patient, while less than 50% were willing to initiate MC treatment for other conditions. Willingness to initiate treatment with MC was low for most indications, while renewal was more acceptable. Our survey revealed PCPs' different opinions and insufficient knowledge regarding the utilization of MC in primary care. These findings emphasize the necessity for continuous medical education regarding MC.